PERSONAL BRANDING: SHAPING AND MAINTAINING A SUCCESSFUL PERSONAL BRAND - Ghaltakhchyan, Siranoush (Armenian Folia Anglistika, 2025)
The present article studies personal branding as a strategic process in which individuals actively shape and promote their unique identities. By creating a personal brand, individuals aim to stand out, shape a likable and trustworthy public image and enhance their professional growth, leading to greater career opportunities. In today’s digital world, the importance of developing a successful personal brand is increasing in order to thrive in the competitive environment. Skillfully presenting the personal brand on social media and various online platforms enables individuals to reach a wider audience, build credibility, foster trust and influence public opinion. The purpose of the research is to examine the efficient strategies that are used for creating a personal brand, the key elements and peculiarities of personal branding. Descriptive and analytical methods are used to analyse the linguistic and extralinguistic means employed by personal brand builders. In particular, Michelle Obama’s personal brand, which exemplifies effective communication and branding strategies in both personal and professional spheres, is studied.